EFFECT OF CALCINATION TEMPERATURE VARIATION ON GREEN SYNTHESIS OF CADMIUM SULFIDE FOR CIPROFLOXACIN PHOTODEGRADATION - Faizah, Aminatul Haq; Gunawan; Khabibi; Wijaya, Roni Adi (International Journal of Research -GRANTHAALAYAH, 2024)
The green synthesis method has been successfully carried out to CdS with tea leaf extract and calcination temperature variation for the application of photocatalytic degradation of ciprofloxacin antibiotic. Variations in calcination at temperatures of 500, 600, and 700 ℃ were carried out to determine the effect of temperature on morphology and elemental composition, crystal structure and size, functional groups, and band gap energy by SEM-EDX, XRD, FTIR, and UV-DRS Spectrophotometer. The SEM-EDX image of the synthesized CdS is smooth and spherical and there is agglomeration with an even distribution of elements. The results of XRD and FTIR characterization showed the CdS peaks. The size of the CdS crystal increased with increasing temperature, namely CdS-600 at 64 nm and CdS-700 at 81.58 nm. The band gap energy value is influenced by the calcination temperature during synthesis with the band gap energy values of CdS-600 2.3 eV and CdS-700 2.38 eV. The percentage of CdS effectiveness with variations in calcination temperature in ciprofloxacin photodegradation is CdS-500 at 32.18%, CdS-600 at 48.72%, and CdS-700 at 8.73%. The optimum condition of CdS synthesis in degrading ciprofloxacin by photocatalytic process occurs at a temperature of 600℃ with a photocatalytic irradiation time under visible light for 120 minutes, a CdS mass of 10 mg, and an initial concentration of ciprofloxacin of 25 ppm. This result demonstrates the potential of an environmentally friendly method that can be applied in wastewater treatment.